Cationic amphiphilic alternating copolymers with tunable morphology. Issue 34 (4th August 2020) - Zhang, Jingling; Yu, Xiaoxi; Zheng, Bingqian; Shen, Jiachun; Bhatia, Surita R.; Sampson, Nicole S.
Abstract : A series of ionic amphiphilic alternating copolymers were characterized via SAXS, TEM and DLS to understand how factors such as covalent structure, and solvent environment affect self-assembly. Abstract : A series of ionic amphiphilic alternating copolymers were characterized via SAXS, TEM and DLS to help understand factors that could potentially affect self-assembly, including the degree of polymerization, the length of hydrophobic spacers between ionic units, the distance between charged groups and polymer backbone, solvent environment and counterions.